Increased QT Interval Dispersion is Associated with Coronary Artery Involvement in Children with Kawasaki Disease - Ehsan Aghaei Moghadam (Oman Medical Journal, 2020)
Objectives: Coronary artery (CA) involvement is the most well known complication of Kawasaki disease (KD). Previous studies have suggested that QT dispersion has a predictive value in diagnosing cardiac ischemia, ventricular arrhythmia, and sudden cardiac death. However, limited data exits regarding the application of QT dispersion in KD. Therefore, we sought to determine whether there is a relationship between QT dispersion and CA involvement in patients with KD. Methods: We performed a cross-sectional study of all consecutive patients with KD who were followed-up at the Pediatric Rheumatology Department (Pediatrics Center of Excellence affiliated to Tehran University of Medical Sciences, Tehran, Iran) from September 2013 to November 2015. Patients who met the criteria for KD, based on the American Heart Association guideline, were enrolled in the study. We collected data regarding patients’ demographics, clinical manifestations, laboratory, and echocardiographic findings. Results: A total of 70 KD patients were identified, including 43 males (61.4%) and 27 females (38.6%). The median age of patients was 21.0 (11.0–48.0) months. We found statistically significant differences between age, gender, and platelet count among patients with and without CA involvement (p < 0.050). Median corrected QT dispersion in patients with CA involvement calculated from 12 leads in the acute phase was significantly higher compared to the non-CA involvement group (108.0 (89.5–138.5) ms vs. 63.0 (54.0–74.5) ms, respectively (p < 0.001)). Conclusions: Prolonged QT dispersion (corrected or non-corrected) during the acute and convalescence phases in patients with KD is associated with coronary involvement.